POSSESIVE PRONOUNCES IN MAYBRAT: A PAPUAN LANGUAGE - OLIVIA URSULA WAREN (Program Magister Linguistik Universitas Udayana, 2007)
Abstract Since the independence time the Indonesian government has decided to make English as one of the compulsory subjects in schools. However, after learning it for six years in senior and high schools, students? English achievement especially in National Final Examination is still poor. This is due to various factors and one of them is the teachers? competence. The competence in fact comprises many aspects such as teachers? academic background, their level of language skill, their degree of language exposures, and still many others. Among those aspects, the ?attrition? of their English is never been touched. The current research tries to look at this phenomenon especially among those teachers who worked at remote areas. The main question to be answered is to what extend the teacher?s English shows the pattern of language attrition? Since the scope of the this kind of research is so wide, the recent study will only discuss the attrition of English in morphological level. This research is a cross-site case study and was carried out using a combination of longitudinal dan cross sectional design. Data elicitation is carried twice with a lapse of six months between each. The corpus is analyzed using T-unit in terms of number of words uttered, number of ?maze?, and number of morphological committed. The difference between the two data elicitations represents the level of language attrition. Kata-kata kunci: Atrisi bahasa, Kedwibahasaan, Pemerolehan bahasa